Peran Mikoriza Arbuskula pada Insidensi Penyakit Busuk Pangkal Batang Lada - Halim Halim; Mariadi Mariadi; La Karimuna; Rachmawati Hasid (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Stem rot or foot rot disease caused by Phytophthora capsici is known as an important constraint on pepper cultivation. Research was conducted to determine the effect of arbuskula mycorhizal fungi (AMF) on incidence of foot rot disease of pepper seedlings. The experiment was done in the net house and arranged using completed randomized design with 6 treatments, i.e. (1) soil infested by P. capsici (TPC) as negative control treatment, (2) sterilized soil (TS) as positive control treatment, (3) TPC with 5 g of AMF, (4) TPC with 10 g AMF, (5) TPC with 15 g AMF, and (6) TPC with 20 g AMF. Observation involved plant height, number of shoots, disease incidence, the percentage of AMF infection on the roots of pepper plants, and pepper plants dependence on AMF. The results showed that the application of AMF at a dose of 20 g per 10 kg of soil effectively suppressed incidence of foot rot disease and improve plant growth